Genomförande och upplevelser av arbetsplatsträffar : Ur medarbetarperspektiv inom Luleå kommun - Engladotter, Riika (2015)
AbstractWorkplace meetings within Luleå Municipality have the aim of increasing the employees` empowerment and responsibility in the workplace. The meetings should be viewed as a tool to anchor the leadership and increase employees’ competencies. In this thesis the employees’ perceptions of their workplace meetings are examined by using leadership theory, Antonovsky`s (2011), Sense of Coherence and Maslow’s (1987) theory of Human Motivation. The research questions are: How are the workplace meetings within Luleå Municipality executed? How does the employee perceive the implementation of the meetings and does workplace meetings contribute to motivation? Ten semi-structured interviews were conducted with employees at Luleå Municipality and the collected data was analyzed using a thematic analysis method. The results show that leadership and structure were interdependent, and that both were needed to accomplish to accomplish a positive perception of the meetings. Through the workplace meetings the employees recognized their own influence and ability to participate in a real sense. The meetings were also viewed as a resource they could use in their own work. Work meetings are meaningful to the employees because they ultimately affect the conditions and quality of the client’s care and additionally motivate the employees themselves to perform during work hours. Validerat; 20150626 (global_studentproject_submitter)